EFFECTIVENESS OF FOOTWEAR AND INSOLE DESIGN TO PREVENT RISK FOOT ULCER IN PEOPLE WITH DIABETES: A SYSTEMATIC REVIEW - Fitriatul Jannah; Sriyono Sriyono; Ni Ketut Alit Armini; Andi Safutra Suraya (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
EFFECTIVENESS OF FOOTWEAR AND INSOLE DESIGN TO PREVENT RISK FOOT ULCER IN PEOPLE WITH DIABETES: A SYSTEMATIC REVIEW Fitriatul Jannah1*, Sriyono1, Ni Ketut Alit Armini1, Andi Safutra Suraya11Faculty of Nursing, Universitas Airlangga , Surabaya, Indonesia*Coresponding Author: fitriatuljannah1997@gmail.com ABSTRACT Introduction: Hyperglycemia is a sign of diabetes mellitus. Long-term uncontrolled hyperglycemia can trigger damage to the nervous system and blood vessels, which can cause diabetic foot ulcer. One of the ways to prevent diabetic foot ulcer by optimizing the use of footwear and insole. Methods: This systematic review aimed to summarize and evaluate the evidence for footwear and insole for the prevention of diabetic foot ulcer. Literature search was conducted for the last 5 years (2018-2023) in English on four databases, Scopus, Science Direct, PubMed, and Web of Science. Using footwear or insoles as intervention in patient with diabetic to prevent of diabetic foot ulcer were reviewed. Writing search results for articles is compiled using checklist and flow diagrams PRISMA. The analysis was descriptive with a narrative approach. Full-text article leaving 8 research articles for review. Results: The result of the article review analysis found innovation in the prevention of diabetic foot ulcers and the prevention of recurrence of diabetic foot ulcers by using footwear and insoles. 5 articles investigated the prevention of diabetic foot ulcers and 3 articles investigated the prevention of recurrence of diabetic foot ulcers using the innovative use of footwear and insoles, all articles stated that the intervention of using footwear and insoles in diabetic prevent diabetic ulcers from occurring and could prevent recurrence of foot ulcers diabetic. Conclusions: The literature review obtained shows that interventions using footwear and insoles can be implemented in people with diabetes mellitus to prevent diabetic foot ulcer. Keywords: Diabetic foot, Foot ulcer, Footwear, and Insoles